Konsepsi lokal-global sebagai basis kultural berkesenian Sanggar Dewata Indonesia - Sucitra, I Gede Arya; Sartini, Sartini (citeus, 2020)
The face of Indonesian art contains multicultural, intercultural, and diverse values in the dialectics of regional arts and global culture. The rise of local culture is often caused by global cultural friction. The attraction and tension between global culture and local culture results in the 'glocalization' of culture. This article aims to explore the values of locality and global culture as a creative foundation for art in the Balinese diaspora art community, Sanggar Dewata Indonesia (SDI) which is culturally and philosophically insightful. The Balinese diaspora gradually has a new cultural identity as a result of the acculturation of Balinese culture with the local culture. Likewise, in the aspect of the language of art, Balinese diaspora artists in Yogyakarta are accommodative, experiencing visual transformation, syncretic, and contain hybridization of cultural values. This study utilizes qualitative methods with a formal study of cultural philosophy through an interpretive approach. The cultural interpretive approach has resulted that the culture and art process of the SDI art community are symbolically the result of the legacy of the collective conception system both in communicating, perpetuating and developing knowledge to attitudes towards artistic life. The mission and vision of SDI includes the spirit of nationalism, Pancasila nationalism, multiculturalism, in order to achieve the international art world, which is more heterogeneous and competitive. Thus the local-global spirit is accompanied by a process of reinterpretation and re-contextualization of a time that presents a thinking discourse, creative vision through creative dialectics that is filled with local-global acculturation shock power towards world-class global art competition.